Using positive deviance in the prevention and control of MRSA infections in a Colombian hospital: a time-series analysis (2017)
Positive Deviance (PD) is a process to achieve a social and cultural change. This strategy has been used for the control of methicillin-resistant Staphylococcus aureus (MRSA) infection in some health institutions in the United States, but has rarely been adopted in institutions from developing countries where resources are limited. We describe our experience of PD in the control of healthcare-associated infections (HAIs) due to MRSA in a Colombian hospital with the aim of reducing HAI rates through a cultural change in processes. A time-series study was conducted based on the MRSA-HAI rate and the number of months with zero MRSA infections before and after application of PD (2001-2012). On comparing the pre-intervention and intervention periods, the mean overall rates of MRSA-HAI was 0·62 and 0·36, respectively (P = 0·0005); the number of months with zero MRSA-HAIs were 3/70 and 12/74 (odds ratio 0·264, 95% confidence interval 0·078-0·897); the percentage of MRSA-HAIs was 53·2% and 41·0%. These results are consistent with other published data. Implementation of PD was associated with a significant reduction of MRSA-HAIs, it did not involve high costs and the changes have been lasting.